GEOLOGICAL STRUCTURE ANALYSIS FOR POTENTIAL LANDSLIDE DISASTER AND MITIGATION AT TANJUNG KERAMAT AREA, GORONTALO - Intan Noviantari Manyoe; Fauzul Chaidir A. Usman; Ivan Taslim; Mohamad Mokoginta; Siti Suhartini S. Napu; Tedy Harianto Salama; Muhammad Ridho Kayambo (Universitas Muhammadiyah Gorontalo, 2020)
Geological structures in the form of joints and faults have big role in landslide disaster. This study aims to analyze the geological structures using stereographic analysis and rosette diagrams and determine the potential landslides that can occur in the research location in order to identify landslide mitigation efforts in the research area. The method used in this research is field observations then followed by stereographic analysis and rosette diagrams, which are one of the diagrams of the presentation of orientation of the geological structures elements. The results showed that the mechanism of landslide mostly caused by the geological structures distribution in the Tanjung Keramat area, especially by joint distribution. Tension joints dominant direction relatively west as well as the slope direction. Stereographic analysis of the shear joints show the type of extensional stress directing relatively North-South. Potential types of landslide that can occur are wedge failures. Appropriate mitigation efforts are by reducing the slope angle and making structural retaining walls to withstand natural slopes and heaps high enough.